Quantum annealing and computation: challenges and perspectives - Chakrabarti, Bikas K.; Leschke, Hajo; Ray, Purusattam; Shirai, Tatsuhiko; Tanaka, Shu (Philosophical Transactions of the Royal Society A-Mathematical Physical and Engineering Sciences, 2023)
In the introductory article of this theme issue, we provide an overview of quantum annealing and computation with a very brief summary of the individual contributions to this issue made by experts as well as a few young researchers. We hope the readers will get the touch of the excitement as well as the perspectives in this unusually active field and important developments there. This article is part of the theme issue 'Quantum annealing and computation: challenges and perspectives'.
CRIS-Team Scopus Importer:2022-12-16
Keywords: NP-hard problems; quantum Ising spin glass; quantum computation; quantum tunnelling; quantum annealing